Botanic Gardens - (:unkn) unknown (Waterman, Trinidad, 2009)
A picture of the well kept grounds of the Botanical Gardens with a fountain at the centre and to the left, part of the Governor General's Residence can be seen.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago; Fountains--Trinidad and Tobago; Garden ornaments and furniture--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Governors--Dwellings--Trinidad and Tobago